Host‐Guest Complexes of [TriPip222], the Piperazine Analogue of [2.2.2]: Prediction of Ion Selectivity by Quantum Chemical Calculations VIII[#]123. Issue 5 (11th March 2016) - Begel, Svetlana; Scheurer, Andreas; Puchta, Ralph; van Eldik, Rudi
Abstract: The selectivity of the cryptand [TriPip222], a per‐aza analogue of cryptand [2.2.2], in which each of the linking arms contains a piperazine ring for the endohedral complexation of metal cations of the I, II, and III main groups and group 12 of the periodic table of elements, was predicted on the basis of DFT [B3LYP/LANL2DZp (LANL2DZp = LANL2DZ augmented with polarization functions on non‐hydrogen atoms)] calculated structures and complex‐formation energies. The cavity size of the studied cryptand is similar to that of [bpy.bpy.bpy], [2.bpy.bpy] and [2.phen.phen], such that the complexation of K + > Na + and of Sr 2+ ≈ Ca 2+ > Ba 2+ are most favorable. The essential flexibility for achieving the selectivity of the cryptand is mainly associated with a twist of the CH2 –Nbridgehead ··· Nbridgehead –CH2 angle and not with the piperazine moiety. Abstract :